2023
DOI: 10.3390/jcm12041524
|View full text |Cite
|
Sign up to set email alerts
|

Current Treatment Landscape for Early Triple-Negative Breast Cancer (TNBC)

Abstract: Triple-negative breast cancer (TNBC) accounts for 15–20% of all breast cancers and is characterized by an aggressive nature and a high rate of recurrence despite neoadjuvant and adjuvant chemotherapy. Although novel agents are constantly being introduced for the treatment of breast cancer, conventional cytotoxic chemotherapy based on anthracyclines and taxanes is the mainstay treatment option for TNBC. Based on CTNeoBC pooled analysis data, the achievement of pathologic CR (pCR) in TNBC is directly linked to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…2 Although different chemotherapy regimens have been developed based on grading systems and pathological diagnoses, clinical treatment of TNBC has long suffered from chemoresistance and relapse. [3][4][5][6] BC, especially TNBC, is a highly heterogeneous malignancy where the complexity of genotype and phenotype determines protein expression, metabolic mechanisms, tumor microenvironment, and ultimately the sensitivity to chemotherapy varying in distinct cell subsets. [7][8][9][10] Therefore, the precision of treatment is considered to meet the challenge of tumor heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although different chemotherapy regimens have been developed based on grading systems and pathological diagnoses, clinical treatment of TNBC has long suffered from chemoresistance and relapse. [3][4][5][6] BC, especially TNBC, is a highly heterogeneous malignancy where the complexity of genotype and phenotype determines protein expression, metabolic mechanisms, tumor microenvironment, and ultimately the sensitivity to chemotherapy varying in distinct cell subsets. [7][8][9][10] Therefore, the precision of treatment is considered to meet the challenge of tumor heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of pembrolizumab plus anthracycline, platinum agents, and taxane as a neoadjuvant regiment is the current standard approach for TNBC, followed by the individualized response or the BRCA gene testing results. It will eventually lead to much complex choices involving olaparib (and its derivatives from poly adenosine diphosphate (ADP) ribose polymerase (PARP) inhibitors), or other immune checkpoint inhibitors (ICIs), e.g., nivolumab, atezolizumab, etc., serving the role of personalized treatment in modern oncology [ 77 , 78 ]. Despite the advancement of those classes as a whole, further exploration revealed that their administration was only effective on specific individuals, as determined by the BRCA status and the programmed death-ligand 1 (PD-L1) expressivity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on the available evidence, platinum-based chemotherapy regimens are not routinely recommended. The regimens could be considered only in patients with high-risk factors such as BRCA mutations ( 90 ).…”
Section: Immunotherapy For Etnbc—controversial Issues and Challengesmentioning
confidence: 99%